COMPETENCE OF COURTS WHO HAVE THE AUTHORITY TO JUDGE DIVORCE CASES BETWEEN DIFFERENT RELIGIONS - Alfiani, Melinda; Suriani Siagian (Fakultas Hukum Universitas Djuanda, 2024)
This study is background to the curiosity of the author regarding the competence of the courts that authored the trial of divorce, in which it is known that the justice in Indonesia under the supreme courtis the common justice, the judicial justice, the military justice and the judiciary of each of the courts has its own jurisdiction in this matter public pretrial and the judicial courts have the same authority in the same way to investigate, prosecute and decide the case of divorce in which the judicial system of religion is consigned to any person who is islamic and a public trial is reserved for people outside of islam then what if the subject is them who after marriage and under the marriage bond of one convert, which court has the authority to prosecute this matter and how the law will result upon the child and treasure of the divorce married couples who after marriage change their religion. The reserach methods adjunct in this study are done by the normatif method, which means that the research is based on studies of laws, govornment regulation, judicial decisions, legal opinions and other books and literature relating to this research. Based on the religio of the marriage that occurs, if the marriage occurs in the islamic religion, then divorce must be based on the rules of islamic law, and in this case, the court of religion is the place.